The Recovery of Lignin from Reed Using Solid-DES Extraction (SDESE) - Ioana Popa-Tudor; Mălina Deșliu-Avram; Lucian Vlădulescu; Diana Constantinescu-Aruxandei; Florin Oancea (Chemistry Proceedings)
The current work presents a sustainable, environmentally friendly method for lignin extraction by applying deep eutectic solvents (DES), which are biodegradable. The Solid-DES extraction (SDESE) method of recovering lignin from reeds is presented. DES based on betaine hydrochloride and lactic acid (BeHCl, LA) was prepared and applied in SDESE at a ratio of 1:20 wt %. Fourier-transform infrared spectroscopy (FTIR) was used to characterize the materials. The DES-extracted lignin (DEL) from the reeds exhibited an interesting structure due to the rearrangement of syringyl, guaiacyl, and parahydroxyphenyl units that occurred as a result of DES breaking the initial raw material structure.